Comment on "Modeling Extreme "Carrington-Type" Space Weather Events Using Three-Dimensional Global MHD Simulations by C. M. Ngwira, A. Pulkkinen, M. M. Kuznetsova, and A. Glocer" - Tsurutani, Bruce T.; Lakhina, G. S.; Echer, Ezequiel; Hajra, Rajkumar; Nayak, Chinmaya; Mannucci, Anthony J.; Meng, Xing (My University, 2018)
An alternative scenario to the Ngwira et al. (2014, https://doi.org/10.1002/2013JA019661) high sheath densities is proposed for modeling the Carrington magnetic storm. Typical slow solar wind densities (~5 cm 3) and lower interplanetary magnetic cloud magnetic field intensities (~90 nT) can be used to explain the observed initial and main phase storm features. A second point is that the fast storm recovery may be explained by ring current losses due to electromagnetic ion cyclotron wave scattering. Plain Language Summary The 1859 Carrington magnetic storm is the largest storm in recorded history. It is used as a model of an "extreme storm" by the U.S. Homeland Security for effects of such an event on the U.S. population. Computer modelers have tried to duplicate the magnetic ground signatures of the storm that were published in Tsurutani et al. (2003, https://doi.org/10.1029/2002JA009504). Some have used extremely high solar wind densities, values which have never been detected in the space age. Here we explain why assumptions of such high densities are unnecessary.
Keywords: Magnetic storms; Solar wind